Psychological Readiness and Enterpreneurial Intentions of Unemployed Graduates: What Difference Can Vocational Psychologists Make? - Eucharia , Obi Ifeoma; Therese , Okeke (African Journal of Education,Science and Technology (AJEST), 2017)
The aim of this study is to ascertain the psychological readiness, entrepreneurial intentions of unemployed graduates and the possible contributions of vocational psychologists in this context. Three research questions and three hypotheses guided the study. Three hundred and twenty-seven unemployed graduates constituted the sample. Questionnaire was used to collect data for the study. Mean, standard deviation, one sample t-test and Pearson Product Moment Correlation Coefficient were used to analyze the data. The researchers found that unemployed graduates had low levels of psychological readiness for entrepreneurship and entrepreneurial intentions. Further, the study revealed a positive correlation between psychological readiness and entrepreneurial intention of unemployed graduates. The contributions of vocational psychologists and limitations for the study were put forward